PON2 Deficiency Leads to Increased Susceptibility to Diet-Induced Obesity - Diana M. Shih; Yonghong Meng; Tamer Sallam; Laurent Vergnes; Michelle L. Shu; Karen Reue; Peter Tontonoz; Alan M. Fogelman; Aldons J. Lusis; Srinivasa T. Reddy (MDPI AG, 2019)
(1) Background: Paraoxonase 2 (PON2) is a ubiquitously expressed protein localized to endoplasmic reticulum and mitochondria. Previous studies have shown that PON2 exhibits anti-oxidant and anti-inflammatory functions, and PON2-deficient (PON2-def) mice are more susceptible to atherosclerosis. Furthermore, PON2 deficiency leads to impaired mitochondrial function. (2) Methods: In this study, we examined the susceptibility of PON2-def mice to diet-induced obesity. (3) Results: After feeding of an obesifying diet, the PON2-def mice exhibited significantly increased body weight due to increased fat mass weight as compared to the wild-type (WT) mice. The increased adiposity was due, in part, to increased adipocyte hypertrophy. PON2-def mice had increased fasting insulin levels and impaired glucose tolerance after diet-induced obesity. PON2-def mice had decreased oxygen consumption and energy expenditure. Furthermore, the oxygen consumption rate of subcutaneous fat pads from PON2-def mice was lower compared to WT mice. Gene expression analysis of the subcutaneous fat pads revealed decreased expression levels of markers for beige adipocytes in PON2-def mice. (4) Conclusions: We concluded that altered systemic energy balance, perhaps due to decreased beige adipocytes and mitochondrial dysfunction in white adipose tissue of PON2-def mice, leads to increased obesity in these mice.